BMSC-Derived Exosomal miR-29a Promotes Angiogenesis and Osteogenesis - Lu, Guo-dong; Cheng, Peng; Liu, Ting; Wang, Zhong (Frontiers in Cell and Developmental Biology, 2020)
Angiogenesis and osteogenesis are tightly coupled during bone modeling and remodeling processes. Here we reported that bone marrow mesenchymal stem cell (BMSC)-derived exosomal miR-29a promotes angiogenesis and osteogenesis in vitro and in vivo. BMSC-derived exosomes (BMSCs-Exos) can be taken up by human umbilical vein endothelial cells (HUVECs) and promote the proliferation, migration, and tube formation of HUVECs. MiRNA-29a level was high in BMSCs-Exos and can be transported into HUVECs to regulate angiogenesis. VASH1 was identified as a direct target of miR-29a, mediating the effects of BMSC-derived exosomal miR-29a on angiogenesis. More interestingly, miR29a-loaded exosomes from engineered BMSCs (miR-29a-loaded BMSCs-Exos) showed a robust ability of promoting angiogenesis and osteogenesis in vivo. Taken together, these findings suggest that BMSC-derived exosomal miR-29a regulates angiogenesis and osteogenesis, and miR-29a-loaded BMSCs-Exos may serve as a potential therapeutic target for osteoporosis.